Slop for Kids: an exploratory study of AI-generated videos for children on YouTube - Goes Mintz, André; Bozzi, Juno (AoIR Selected Papers of Internet Research, 2026)
This paper investigates AI-generated videos for children on YouTube through an exploratory study. Using a digital methods approach, we compiled two datasets of videos from 2022 to 2024, in English and Portuguese, containing references to both “AI” and “children.” From these, we manually selected and analyzed a subset of AI-generated children’s videos, describing their characteristics and discussing implications. Our findings reveal a growing presence of AI-generated children’s videos, mainly featuring music and stories, with also educational and religious content. As a secondary finding, we have also identified numerous tutorial-style videos promoting the monetization of AI-generated content, reflecting broader trends in low-effort, engagement-driven video production. Despite AI’s increasing role in content creation, most AI-generated children’s videos did not achieve high view counts, with a few exceptions that raise questions about AI’s contribution to engagement and virality. The study also highlights the challenges of defining AI-generated content, as many videos exist on a spectrum of AI usage rather than being entirely machine-produced. Our findings highlight the need for further research on AI’s influence on children’s media consumption, the role of automation in shaping content, and the implications for the quality and diversity of children’s online media.